2016
DOI: 10.1155/2016/9706720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment Delay, Stroke Type, and Thrombolysis on the Effect of Glyceryl Trinitrate, a Nitric Oxide Donor, on Outcome after Acute Stroke: A Systematic Review and Meta-Analysis of Individual Patient from Randomised Trials

Abstract: Background. Nitric oxide (NO) donors are a candidate treatment for acute stroke and two trials have suggested that they might improve outcome if administered within 4–6 hours of stroke onset. We assessed the safety and efficacy of NO donors using individual patient data (IPD) from completed trials. Methods. Randomised controlled trials of NO donors in patients with acute or subacute stroke were identified and IPD sought from the trialists. The effect of NO donor versus control on functional outcome was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 39 publications
0
47
1
Order By: Relevance
“…Four small clinical studies of glyceryl trinitrate (GTN), a NO donor that can be administered transdermally, in patients with recent stroke found that it reduced blood pressure (an independent risk factor for a poor outcome (22)(23)(24)) and pulse pressure; had no effects on middle cerebral artery blood flow velocity, cerebral blood flow, or intracranial pressure; did not alter platelet activity (so GTN can be given in ICH); (14,(25)(26)(27) (28); however, functional outcome was improved in those patients recruited within 6 hours (a prespecified subgroup) (28,29), this result mirroring that seen in RIGHT (30).…”
Section: Nitric Oxide Donorsmentioning
confidence: 82%
“…Four small clinical studies of glyceryl trinitrate (GTN), a NO donor that can be administered transdermally, in patients with recent stroke found that it reduced blood pressure (an independent risk factor for a poor outcome (22)(23)(24)) and pulse pressure; had no effects on middle cerebral artery blood flow velocity, cerebral blood flow, or intracranial pressure; did not alter platelet activity (so GTN can be given in ICH); (14,(25)(26)(27) (28); however, functional outcome was improved in those patients recruited within 6 hours (a prespecified subgroup) (28,29), this result mirroring that seen in RIGHT (30).…”
Section: Nitric Oxide Donorsmentioning
confidence: 82%
“…An individual patient data meta-analysis using data from the five completed GTN trials (GTN-1/2/3, ENOS, RIGHT, n  = 4197) supported the findings that treatment with GTN within 6 h of onset ( n  = 312), but not later, improved functional outcome and secondary outcomes across a range of domains: cognition; death; disability; mood; and quality of life (Table 2) [50]. The time-dependent effect on functional outcome was seen in both IS and ICH; a finding supported by a subgroup analysis of participants with ICH from the ENOS trial [51].…”
Section: Nitric Oxide Donors and Acute Strokementioning
confidence: 83%
“…As previously alluded to, GTN positively influenced several clinical outcomes when given early in both IS and ICH [50]. Whether GTN has the same effects in patients with lacunar syndromes, lacunar strokes or small vessel disease is unclear and further analysis is required.…”
Section: Unanswered Questionsmentioning
confidence: 97%
See 2 more Smart Citations